A Modeling Study on Population Dynamics of Jellyfish Aurelia aurita in the Bohai and Yellow Seas - Zhang, Haiyan; Zhang, Guangyue; Lan, Yifan; Xiao, Jingen; Wang, Yuheng; Song, Guisheng; Wei, Hao (Frontiers in Marine Science, 2022)
Jellyfish blooms have become a marine environmental issue with detrimental effects on marine ecosystems around the world. The jellyfish Aurelia aurita is one of dominant species of blooms worldwide and also in the Bohai and Yellow Seas (BYSs) of China. To investigate population dynamics and controlling factors on population biomass, a complex population-dynamic model is developed for jellyfish of A. aurita in the BYSs that includes three components, namely, a three-dimensional coupled physical–biogeochemical model, a Lagrangian particle-tracking model, and an energy balance model for the jellyfish life cycle. By comparison, the model well reproduces the individual growth and seasonal evolution of A. aurita population. During individual growth period, the temperature is a key factor controlling growth and dry weight, characterized by a nearly linear growth rate. Longer period tends to favor larger medusa size and further to promote the biomass. The yearly peak biomass shows interannual variations that are controlled by the jellyfish magnitude, food concentration, and effective accumulative temperature of growth, with their contributions quantified through statistical analyses. Only considering the effect of temperature, the yearly peak biomass can be obtained through the durations of suitable temperature ranges for strobilization and individual growth that determines the magnitude and the averaged individual weight, respectively, with longer strobilation duration leading to higher magnitude. The simplified statistical relationships would favor to understand the temperature control on population dynamics of A. aurita.